ANALYSIS OF POLITICAL PARTIES COMMUNICATION MANAGEMENT IN INDONESIAN PROVINCIAL GOVERNOR DIRECT ELECTION (2017 DKI JAKARTA GOVERNOR ELECTION CASE STUDY) - Razak Mozin , Marta Sanjaya,Yusa Djuyandi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In general, the incumbent wins every local leaders election (Pilkada), and is supported by the ruling political party (government). The defeat of Ahok-Djarot candidate pair from Anis-Sandi candidate pair in the 2017 DKI Jakarta governor election is interesting to study, especially with regard to political communication. The management of political messages by party elites and candidates/nominees is one of the important factors in achieving victory. The case of religious blasphemy committed by Ahok was considered a factor in his failure. Therefore, political parties and candidates who will advance in the regional head election can manage political communication effectively, in order that not only the victories are obtained but the negative impacts of the election such as black campaign, hoaxes, damage, chaos, and even casualties can be avoided. The method in this research is a case study. This method is carried out naturally, holistically and with in-depth study to answer several problems. Natural means that the data and information were obtained naturally from some party elites. Holistic means that the data are from parties involved in the election as one unit. In addition, in-depth study means that the data is studied in depth until it finds answers to the problems being studied. The results of the study show that the management of political communication by Anies-Sandi candidate pair, especially its political messages, ideas, concepts and programs, is one of the factors and keys to success in the 2017 DKI Jakarta governor election.